An experimental indicator to forecast turning points - Dalton, Padraig; Keogh, Gerard (Statistical and Social Inquiry Society of Ireland, 2000)
The Business Cycle in Gross Domestic Product (GDP) describes the recurring cycles of expansion and slowdown in overall economic well being. A Composite Leading Indicator (CLI) is a small group of important economic indicators that can be used to predict likely future phases, or turning points, of the business cycle. The business cycle in the Irish economy is extracted in this paper using a combination of symmetric Henderson Moving Average filters. These filters are also applied to a broad range of economic indicator series that are then combined together, on the basis of cyclical conformity and lead time, to form an Experimental Composite Leading Indicator (XCLI). This exercise is undertaken for both annual and interpolated quarterly GDP data. The ability of the XCLI to predict future phases in the Irish business cycle in GDP is examined.
Read before the Society, 9 March 2000
Keywords: Economic time series; Henderson moving averages; Business cycle; Turning points; Cyclical conformity; Leading indicator; 314.15